2019
DOI: 10.1002/jaba.556
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of functional analysis methods of inappropriate mealtime behavior

Abstract: Investigators have evaluated two procedural variations for conducting a functional analysis of inappropriate mealtime behavior exhibited by children with feeding problems. One method involves prompting bites only in the escape condition (e.g., Najdowski et al., 2008). Another method involves prompting bites across all conditions (e.g., Piazza et al., 2003). We assessed the food refusal of 3 children diagnosed with a feeding disorder by comparing the two variations. The two methods resulted in different outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 13 publications
0
22
0
Order By: Relevance
“…In contrast, the Najdowski et al procedures could be prone to false‐negative identification of a positive reinforcement function because relevant discriminative stimuli (i.e., bite presentation) are absent across conditions except during the test for escape (e.g., attention could serve as a reinforcer for inappropriate mealtime behavior when a bite is presented but not when the child is left alone). Bachmeyer, Kirkwood, Criscito, Mauzy, and Berth () confirmed this discrepancy in functional analysis outcomes for two of three children when the two methods were directly compared. However, when the relative effects of extinction procedures were compared during treatment, both escape extinction and attention extinction were necessary to reduce inappropriate mealtime behavior, suggesting that the method based on Najdowski et al was prone to false‐negative identification of a positive reinforcement function.…”
Section: Discussionmentioning
confidence: 79%
“…In contrast, the Najdowski et al procedures could be prone to false‐negative identification of a positive reinforcement function because relevant discriminative stimuli (i.e., bite presentation) are absent across conditions except during the test for escape (e.g., attention could serve as a reinforcer for inappropriate mealtime behavior when a bite is presented but not when the child is left alone). Bachmeyer, Kirkwood, Criscito, Mauzy, and Berth () confirmed this discrepancy in functional analysis outcomes for two of three children when the two methods were directly compared. However, when the relative effects of extinction procedures were compared during treatment, both escape extinction and attention extinction were necessary to reduce inappropriate mealtime behavior, suggesting that the method based on Najdowski et al was prone to false‐negative identification of a positive reinforcement function.…”
Section: Discussionmentioning
confidence: 79%
“…Additionally, clinicians often teach caregivers to implement escape and attention extinction as a treatment package. However, evaluating the specific role of attention in the maintenance of inappropriate mealtime behavior can be important (Bachmeyer et al, 2019). For example, although clinicians would not typically teach caregivers to provide attention following instances of inappropriate mealtime behavior, teaching caregivers to withhold escape and attention for inappropriate mealtime behavior (i.e., escape and attention extinction) when only escape is identified as a reinforcer, may be unnecessary.…”
Section: Discussionmentioning
confidence: 99%
“…Attention was the second most common caregiver consequence. Fourth, results of studies on functional analysis of inappropriate mealtime behavior have shown that escape functions as negative reinforcement for inappropriate mealtime behavior for most children with feeding disorders (Bachmeyer et al, 2019; Girolami & Scotti, 2001; Najdowski et al, 2008; Piazza et al, 2003). These data suggest that if inappropriate mealtime behavior reemerges, caregivers are likely to deliver escape and possibly attention and these consequences are likely to function as reinforcement.…”
mentioning
confidence: 99%